ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK SERTA KONSEP DIRI SISWA DI SMA INKLUSI - Dinda Nur Kur'aeni; Yuniar Damiyanti; Wahyu Hidayat (Departement of Mathematics Education, 2019)
This study aims to determine the communication skills and self-concept of students. This study involved 11th grade from one of the Inclusion Senior High Schools in Cimahi City. Inclusive Education is a system of education that provides opportunities for all students who have abnormalities and have potential intelligence and / or special talents to participate in education or learning in an educational environment together with students in general. This research method uses descriptive qualitative. The instruments used were mathematical communication test questions. As for self-concept, the instrument used was a questionnaire with a modified Likert scale ranging from 1-4. To examine the mathematical communication skills possessed by the eleven students provided 4 as a test instrument. Based on data obtained from the results of the study, the average criteria for mathematical communication ability was 24.55% (low). As for the self concept, the classification criteria are NA> 60 (strong). This shows that there is no positive relationship between mathematical communication skills and self-concept of students